Enhancing maize (Zea mays) productivity through integrated soil fertility management: a participatory approach in the degraded soils of Kigoma, Tanzania - Lelei, David K.; Sultan, Masoud S.; Kuboja, Nicholaus M.; Mwangi, Lukelysia N.; Sinclair, Fergus (Frontiers in Agronomy, 2025)
Maize is a staple cereal for countries in sub-Saharan Africa, characterized by a low average yield of less than 1 ton per hectare in many smallholder farms across these countries. The low maize yield is attributed to poor soil fertility, poor crop management practices, poor post-harvest handling techniques, and erratic rainfall. The objective of the study was to investigate the effects of selected integrated soil fertility management (ISFM) technologies on soil chemical properties and maize yields following the use of the InPaC-S (Portuguese for Integração Participativa de Conhecimentos sobre Indicadores de Qualidade do Solo or Participatory Knowledge Integration on Indicators of Soil Quality) methodological approach. This methodological approach was employed to mobilize farmers through workshops and field experiments using selected integrated soil fertility management options: use of organic manure, lime, and nitrogen, phosphorus, and potassium (NPK) fertilizer. The experiment was laid out in a randomized complete block design (RCBD) with three replications, including manure, lime, NPK, lime + manure, manure + NPK, lime + NPK, and control. The results revealed significant differences between the treatments (p<0.001) and sites (p<0.001) for all studied growth parameters. The use of lime + NPK significantly increased maize yields by 149% (p<0.001) compared to the control and influenced electrical conductivity, cation exchange capacity (CEC), organic carbon, total nitrogen, total phosphorus, and exchangeable bases. In turn, the cost of maize production (USD/ha) varied between treatments, ranging from 419.8 to 630.9 USD in the control and lime + NPK, respectively. The major costs included inorganic fertilizers, weeding, and land preparation, with inorganic fertilizers contributing the most to the total production cost. The net revenue in USD/hectare for the treatments was significantly (p<0.001) highest for lime + NPK ($1,260.90) and lowest for the control ($339.60). A sensitivity analysis was performed on the net income, and the results suggest that as fertilizer costs increase, there comes a point where their use is no longer economically viable. Consequently, different ISFM options, such as the combination of lime and manure, lime alone, and manure alone, become relevant. This empirical evidence concludes that the use of other integrated soil fertility management options will translate to a long-term improvement in food security and better livelihoods among communities. Future research should focus on scaling up/out these ISFM practices to further improve soil health, increase crop yields, and promote better livelihoods in sub-Saharan Africa.